Nanocrystallization and optical properties of CsPbBr3−xIx perovskites in chalcogenide glasses. Issue 8 (July 2021) - Long, Nengbing; Fu, Yanqing; Xu, Tianxiang; Ding, Dashuang; Zhang, Shaoqian; Sun, Shengzhi; Kang, Shiliang; Xu, Tiefeng; Dai, Shixun; Nie, Qiuhua; Lin, Changgui
Abstract: The confinement of CsPbX3 (X = Cl, Br, and I) perovskite nanocrystals (NCs) in a stabilized inorganic glass matrix is a new strategy for improving their long-term stability and promoting their applications in the optoelectronic field. Here, in situ nanocrystallization strategy is developed to precipitate CsPbBr3− x I x NCs with arbitrary I/Br ratio among an elaborately designed GeS2 –Sb2 S3 -based chalcogenide glass matrix. Spherical CsPbBr3− x I x NCs are homogeneously distributed in the glass matrix after thermal treatment. The photoluminescence (PL) spectra show that the emission peaks of CsPbBr3− x I x NCs can be tuned from 570 nm to 722 nm with the replacement of Br by I. The fs transient absorption (TA) spectra reveal that there exists some structural defects in the NCs, leading to short PL decay life. This work would shed light on confining CsPbX3 NCs into glassy matrices, facilitating their future applications in photoelectronic fields.